The conventions concerning weapons of mass destruction and the extent of their application to the depleted uranium weapon - Issa, Aqila Hadi; Abdul Wahab, Harlida; Abdullah, Nor Anita (2017)
In view of the features and the dangerous effects of weapons of mass destruction, these weapons have been organized under international conventions. Some of these weapons have been internationally banned such as chemical and biological weapons. Others have been restricted like the nuclear weapons.Depleted uranium, which defined as a secondary result of uranium mining in nuclear reactors, have the same characteristics and effects of the latter weapons, but they have not been covered by any international convention so far.This constitutes a shortage in the international legislation requiring a treatment.This paper will be conducted through doctrinal approach; data will be collected through secondary source by examining the contribution of scholars in the field of law.The current research will try to clarify the possibility of application of conventions on weapons of mass destruction with respect to depleted uranium weapons